2009
DOI: 10.1111/j.1469-1809.2009.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Ability of Tree‐Based Methods and Logistic Regression for the Detection of SNP‐SNP Interaction

Abstract: SummaryMost common human diseases are likely to have complex etiologies. Methods of analysis that allow for the phenomenon of epistasis are of growing interest in the genetic dissection of complex diseases. By allowing for epistatic interactions between potential disease loci, we may succeed in identifying genetic variants that might otherwise have remained undetected. Here we aimed to analyze the ability of logistic regression (LR) and two tree-based supervised learning methods, classification and regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…This good performance is documented in several independent comparison studies implementing different simulation settings [26,54,73,17]. In these studies, however, standard VIMs (either Gini or permutation) are used to rank the SNPs.…”
Section: Predictors Involved In Interactionsmentioning
confidence: 97%
“…This good performance is documented in several independent comparison studies implementing different simulation settings [26,54,73,17]. In these studies, however, standard VIMs (either Gini or permutation) are used to rank the SNPs.…”
Section: Predictors Involved In Interactionsmentioning
confidence: 97%
“…Multiple studies have compared RF to other parametric and computational methods, showing the variable importance scores to be more powerful and stable than other current approaches ([García-Margariños et al 2009;Lunetta et al 2004;McKinney et al 2006;Nicodemus et al 2007]. In addition to gene x gene interaction RF has also been used to successfully detect gene x environment interactions [Maenner et al 2009].…”
Section: Interaction Detectionmentioning
confidence: 99%
“…In comparison, García-Magariños et al [4] found that RF and CART performed as well as logistic regression and MDR when there were SNPs with marginal effects and unknown interactions in the presence of a large number of noise SNPs. In pure interaction models, they found that RF performed as well as MDR especially with large sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Lunetta et al [3] show that RF is more efficient than Fisher's exact test for ranking true disease-associated SNPs. García-Magariños et al [4] compare the top-rated SNP as chosen by RF, classification and regression trees (CART), logistic regression, and multifactor dimensionality reduction (MDR) over numerous settings including several with missing data, whereas Szymczak et al [5] compare RF and ensemble methods to penalized regression and network analyses. Jiang et al [6] use RF Gini variable importance measure to rank SNPs before implementing a forward feature selection algorithm to choose a subset of SNPs and then adopt a hierarchical procedure (unrelated to RF) to determine the statistical significance of the subset.…”
mentioning
confidence: 99%